UPAYA SEKOLAH DAN ORANG TUA DALAM MENDUKUNG PEMBELAJARAN ANAK DENGAN KONDISI RUMAH RUSAK PASCABANJIR - Erlida Mayanti Hasibuan; Indah Marlina Harahap; Suci Cantika Airin (Yayasan Baitul Hikmah al-Zain, 2026)
This study discusses the efforts of schools and parents in supporting children’s learning when their homes are damaged after a flood. Flood disasters often have serious impacts on the continuity of children’s education, affecting not only learning facilities but also their psychological well-being and motivation to continue studying. Children who are affected often lose proper housing and experience emotional distress, making them in need of comprehensive support from their surroundings, particularly schools and families. This research uses the library research method, which involves reviewing various literature sources such as books, journals, research reports, and scientific articles related to children’s education in post-disaster contexts. This method was chosen because it allows the researcher to examine theories and previous findings in depth, providing a conceptual understanding of strategies and the roles of different stakeholders in restoring education after a flood. The findings indicate that schools play a strategic role as institutions that focus not only on academic instruction but also on providing emotional, social, and moral support for students. Teachers play a crucial role in creating a safe and empathetic learning environment and in rebuilding children’s motivation through flexible and contextual learning approaches. Meanwhile, parents contribute by offering moral support, creating a conducive learning atmosphere at home, and maintaining active communication with the school. Collaboration between schools and parents is identified as the key factor in restoring children’s learning enthusiasm after a flood, as well as in fostering resilience and educational awareness that help them face future challenges with strength and confidence.